Preparation of Crown‐Ether‐Functionalized Polysulfone Membrane by In Situ Surface Grafting for Selective Adsorption and Separation of Li+. Issue 11 (17th March 2020) - Li, Jixue; Yi, Hong; Wang, Mingxia; Yan, Feng; Zhu, Quanji; Wang, Shouhe; Li, Jianxin; He, Benqiao; Cui, Zhenyu
Abstract: In order to develop an effective and environment‐friendly method for selective adsorption of Li +, a recyclable polysulfone surface graft 4'‐aminobenzo‐12‐crown‐4‐ether (PSf‐sg‐AB12 C4) membrane was prepared via non‐solvent induced phase separation method and in situ surface grafting through nucleophilic substitution. The surface chemical compositions and the morphologies of the PSf‐sg‐AB12 C4 were systematically verified by X‐ray photoelectron spectra (XPS) and scanning electron microscopy (SEM). The dynamic adsorption process of PSf‐sg‐AB12 C4 for Li + was well described by the pseudo‐second‐order kinetics model, and the maximum equilibrium adsorption capability was 51.99 mg⋅g ‐1 . Moreover, the PSf‐sg‐AB12 C4 membrane displayed good selectivity for Li +, meanwhile the selective separation factors (α) of Li + to K +, Na +, Ca 2+ and Mg 2+ were 38.43, 33.13, 27.11 and 3.42, respectively. These selective adsorption results were verified by the density functional theory (DFT) calculations. Additionally, the regenerated adsorption amount of the PSf‐sg‐AB12 C4 toward Li + after 10 cycles of adsorption/desorption was 90.37% of initial adsorption cycle. Abstract : Lithium ion selective polysulfone surface graft 4'‐aminobenzo‐12‐crown‐4‐ether (PSf‐sg‐AB12 C4) membrane was prepared by in situ surface grafting through nucleophilic substitution. Results indicated that the functionalized membrane exhibited excellent selectivity adsorption performance for Li + compared with other co‐exiting ions such as Na +, K +, Ca 2+ and Mg 2+ .